Comprehensive analysis of chromosome 8 abnormalities and its prognostic value in patients with uveal melanoma - V. A. Yarovaya; A. A. Yarovoy; L. V. Chudakova; I. A. Levashov; A. R. Zaretskiy (Успехи молекулярной онкологии, 2022)
Introduction. Uveal melanoma ability to metastasize depends on a few prognostic factors. The genetic ones are considered to be the most significant. The role of disorders of the short arm of chromosome 8 (8p), as well as a combination of changes in 8p and the long arm of this chromosome (8q) in the development of metastatic lesions in this pathology remains insufficiently studied.The study objective – to evaluate the prognostic value of chromosome 8 abnormalities in patients with uveal melanoma.Materials and methods. We analyzed 2 retrospective groups of patients who underwent enucleation for uveal melanoma, statistically homogeneous in the main clinical parameters. Group 1 included patients without signs of metastases (n = 41) with an average follow-up period of 71 months, Group 2 included patients with detected metastases (n = 51) and an average follow-up period of 21 months Chromosome abnormalities were tested by multiplex ligation-dependent probe amplification.Results. Three- and five-year survival in patients with uveal melanoma without 8p deletion were 64 and 54 %, respectively; with 8p deletion significantly lower – 25 and 6 %, respectively. The same survival rates in patients with uveal melanoma with 8q amplification were 43 and 26 %, respectively, whereas in patients without 8q amplification they were significantly higher – 80 and 74 %, respectively. In patients with uveal melanoma harbouring both abnormalities, 3- and 5-year survival rates were 26 and 7 %, whereas isolated 8q amplification was associated with 47 and 35 % survival, respectively. These survival rates differ greatly and significantly: hazard ratio 3,26 (95 % confidence interval 1,86–5,69) and 6,89 (95 % confidence interval 2,67–17,73), respectively (р <0,0001).Conclusion. The findings support comprehensive evaluation of chromosome 8 abnormalities as a substantial part of uveal melanoma prognostication. 8q amplification, 8p deletion, combination of these abnormalities and its role in uveal melanoma malignity should be further discovered. Further research in this direction is needed.